2022
DOI: 10.1093/plcell/koac047
|View full text |Cite
|
Sign up to set email alerts
|

The maize single-nucleus transcriptome comprehensively describes signaling networks governing movement and development of grass stomata

Abstract: The unique morphology of grass stomata enables rapid responses to environmental changes. Deciphering the basis for these responses is critical for improving food security. We have developed a planta platform of single nucleus RNA-sequencing by combined fluorescence-activated nuclei flow sorting, and used it to identify cell types in mature and developing stomata from 33,098 nuclei of the maize epidermis. Guard and subsidiary cells displayed differential expression of genes, besides those encoding transporters,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 154 publications
0
21
0
Order By: Relevance
“…More recently, it was found that CYCLING DOF FACTOR 5 (CDF5) and REPRESSOR OF GA (RGA) have potential roles in the early development and function of leaf veins in cotyledons (Liu et al, 2022b). Sun et al (2022a) identified cell types in mature and developing stomata of maize (Zea mays) epidermis-enriched tissue and found that guard cells (GCs) and subsidiary cells (SCs) displayed differential expression of genes, which, besides those encoding transporters, were involved in the abscisic acid, CO 2 , Ca 2+ , starch metabolism, and blue light signaling pathways.…”
Section: Commercial Microfluidics Technologies Such As the 10xmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, it was found that CYCLING DOF FACTOR 5 (CDF5) and REPRESSOR OF GA (RGA) have potential roles in the early development and function of leaf veins in cotyledons (Liu et al, 2022b). Sun et al (2022a) identified cell types in mature and developing stomata of maize (Zea mays) epidermis-enriched tissue and found that guard cells (GCs) and subsidiary cells (SCs) displayed differential expression of genes, which, besides those encoding transporters, were involved in the abscisic acid, CO 2 , Ca 2+ , starch metabolism, and blue light signaling pathways.…”
Section: Commercial Microfluidics Technologies Such As the 10xmentioning
confidence: 99%
“…In addition to the applications in Arabidopsis primary root tips, scRNA‐seq has been applied to study other dicots and monocots, as well as in leaves, inflorescences, and other tissues (Sun et al., 2022a; Zong et al., 2022). More recently, it was found that CYCLING DOF FACTOR 5 (CDF5) and REPRESSOR OF GA (RGA) have potential roles in the early development and function of leaf veins in cotyledons (Liu et al., 2022b).…”
Section: Single‐cell Transcriptomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Are guard cells primarily regulated, and subsidiary cells merely responsive to the changes in the adjacent guard cells, perhaps accumulating potassium and calcium the guard cells export into the apoplast? Previous analyses have identified proteins shared between grass subsidiary and guard cells, as well as those that are unique to each cell type (Majore et al, 2002;Mumm et al, 2011;Nguyen et al, 2017;Wang et al, 2019b;Sun et al, 2022). Nonetheless, whether the two cell types have unique signaling mechanisms, and what if any coordination exists between subsidiary cells and guard cells is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a series of developmental processes in Arabidopsis had been explored at single cell resolution, such as the development of root tips (Denyer et al ., 2019 ; Jean‐Baptiste et al ., 2019 ; Shahan et al ., 2022 ; Wendrich et al ., 2020 ; Zhang et al ., 2019 ), lateral root (Gala et al ., 2021 ), vegetative shoot apex (Zhang et al ., 2021b ), stomatal cell lineage (Liu et al ., 2020 ), developing leaf (Kim et al ., 2021 ; Liu et al ., 2022a ; Lopez‐Anido et al ., 2021 ; Tenorio Berrio et al ., 2022 ) and vein pattern in the cotyledons (Liu et al ., 2022b ). At the same time, scRNA‐seq has also been widely used in other plants, including rice (Liu et al ., 2021b ; Wang et al ., 2021b ; Zhang et al ., 2021a ; Zong et al ., 2022 ), corn (Li et al ., 2022 ; Ortiz‐Ramirez et al ., 2021 ; Satterlee et al ., 2020 ; Sun et al ., 2022 ; Xu et al ., 2021 ), peanut (Liu et al ., 2021a ), tea plant (Wang et al ., 2022 ), tomato (Omary et al ., 2022 ) and poplar (Chen et al ., 2021 ; Li et al ., 2021 ; Xie et al ., 2022 ). These studies provide new insights into heterogeneity of gene expression between different cell types, and molecular trajectory of cell differentiation during development.…”
Section: Introductionmentioning
confidence: 99%